Cyclin-Dependent Kinase 6 Identified as the Target Protein in the Antitumor Activity of Tetrastigma hemsleyanum - Wei, Chaoguang; Zhao, Yuxiang; Ji, Tao; Sun, Yong; Cai, Xudong; Peng, Xin (Frontiers in Oncology, 2022)
Tetrastigma hemsleyanum Diels et gilg (T. hemsleyanum) has antitumor activity in vitro and in vivo. It is widely used as an adjuvant drug for chemotherapy in tumor patients. In this study, we found 124 potential target proteins of T. hemsleyanum in vivo through network pharmacological analysis, and then screened 5 hub genes through protein-protein interaction (PPI) network analysis and molecular complex detection analysis (MCODE). It was verified by cell culture and experimental methods of intervention treatment of aqueous extract of T. hemsleyanum, AKR1C1, MET, PTK2, PIK3R1and CDK6 are the target proteins involved in the regulation of T. hemsleyanum in vivo. Then, through pan-cancer analysis of hub genes, from hub gene expression, prognosis, tumor immune cell infiltration analysis, correlation score of immune checkpoint gene expression, correlation analysis of microsatellite instability, correlation analysis of tumor mutational burden, correlation analysis of tumor neoantigen. The correlation analysis of immune microenvironment confirmed that CDK6 and MET were potential targets for T. hemsleyanum to exert antitumor activity, and had antitumor activity in ACC, CESC, LGG and PAAD. Combined with the results of gene set enrichment analysis, it is found that T. hemsleyanum can play an anti-tumor function as a potential cell cycle checkpoint inhibitor, and has the activity of tyrosine kinase receptor inhibitor to inhibit the expression of proto oncogene MET. In addition, combined with the analysis of immune and mutation correlation in pan-cancer, it is found that T. hemsleyanum has potential biological functions of immune regulation and interfering with the stability of tumor genome, which is worthy of further study.